Physical evaluation of lipstick contains encapsulated beet (Beta vulgaris linn.) root water extract in maltodextrin - Hilda Srivaliana Ilham; Anita Sukmawati (Universitas Ahmad Dahlan, 2020)
The natural dyes from beet (Beta vulgaris Linn) (BV) roots can be used as coloring agents in lipsticks. However, the dye has low stability in high temperature and light and can be oxidized by air. The dye was encapsulated into a microparticle (MP) using maltodextrin (MD) as a matrix to improve color stability. The research's objective was to evaluate the effect of various MD concentrations in encapsulated BV root extract towards physical characterizations of MP and lipsticks, including pH, lipstick hardness, melting point, and color stability. The BV roots water extract was obtained by grinding BV root into a juice and then dried using a freeze dryer. The encapsulation of the BV root extract was using MD as a matrix with a ratio of 1:5 BV dried extract to MD. The MD solution concentrations used in this experiment were 25%, 50%, and 75% (w/v). The result showed that the morphology of MPs resulting from the encapsulation is amorphous. Lipsticks were characterized by pink color and had shape according to the lipstick mold. The lipstick color changed to brown on the seventh day and faded on the 28th day. The variation of MD concentrations during MP preparation did not significantly influence the lipstick's pH value, hardness and melting point.